Effects of a State Mandated Policy (Site-Based Councils) and of Potential Role Incumbents on Teacher Screening Decisions in High and Low Performing Schools. - Young, I. Phillip; Miller-Smith, Kimberly (Education Policy Analysis Archives, 2006)
Some states have viewed teacher selection as a means of improving student performance and have mandated the use of site-based teacher councils. To assess the utility of this legislative action, an experimental study was conducted. This study uses a 2X3X2 factorial design that varies state legislation, role of the decision maker, and academic performance of the school site. Credentials of hypothetical teacher candidates were evaluated as if screening for a vacant position, and evaluations were submitted to a MANOVA. Results indicate that legislated alterations in the teacher-selection process failed to have any substantial effects on outcomes in the screening of teacher candidates for elementary school positions. Although screening decisions were found to be the same for participants affiliated with both low- and high-performing school districts, teachers were more appreciative of candidate’s credentials than either principals or parents.